A Local Transition Adaptive Structured Mesh Generation Method for Finite Difference Time Domain Simulation - Cao, Zixuan; Mou, Chunhui; Wang, Chenghao; Chen, Juan; Li, Shaolong; Zhao, Cuirong; Yin, Yuemeng (Applied Computational Electromagnetics Society Journal (ACES), 2024)
In this paper, a local transition adaptive structured mesh generation method is proposed for finite difference time domain (FDTD) simulation. This innovative approach can automatically identify the location of the medium interfaces and boundaries based on the triangular facet of the target, and subsequently divide the entire computational domain into numerous subregions. In the subregions, uniform mesh lines are initially placed in accordance with the numerical requirement of FDTD method. Subsequently, part of these meshes are refined based on target structure. Finally, local transition processing is performed for meshes with large variations at the boundaries of neighboring subregions, so that there is no rapid change in mesh size in the boundary position. Different from the existing automatic non-uniform mesh generation methods, the method proposed only adds transition meshes at the medium interfaces and boundaries instead of placing global gradient meshes, so it can greatly reduce the mesh quantity and simplify the mesh generation process. Two classical models of inverted-F antenna and cross-slot frequency selective surface are employed as examples to verify the validity of our method. Simulation results demonstrate that this generation method can achieve nearly equivalent simulation accuracy as the global gradient mesh generation method with a markedly reduced number of meshes.